Analisis Neraca Air waduk Saguling Kabupaten Bandung Barat Provinsi Jawa Barat - Heuristik Ifowaa Halawa; Olga Catherina Pattipawaej (Journal of Smart Technology and Engineering, 2025)
Population growth and regional development in an area cause water needs to continue to increase because the fulfillment of food needs and population activities are always closely related to water needs. One of the water providers used by the community is a reservoir. Saguling Reservoir is a reservoir located in Saguling Village, West Bandung Regency, West Java Province, which has several benefits such as providing drinking water, irrigation, flood control and tourist attractions. In this Final Project, it was discussed about the availability of water in the Saguling Reservoir by conducting research in the form of water balance analysis. The purpose of this study is to provide an overview of water availability in Saguling Reservoir by considering inflow from rivers, outgoing discharge, rainfall, and evaporation using 2022 data. The results of the water balance analysis show that the water availability of Saguling Reservoir can meet water needs for various purposes every month in 2022. Further water balance analysis by considering seepage and infiltration that occurs in Saguling Reservoir. Keywords: balance of water, discharge, precipitation, evaporation.